Production of Succinic Acid From Basfia succiniciproducens - D’ambrosio, Sergio; Alfano, Alberto; Cimini, Donatella (Frontiers in Chemical Engineering, 2021)
Basfia succiniciproducens is a facultative anaerobic capnophilic bacterium, isolated from rumen, that naturally produces high amounts of succinic acid by fixing CO2 and using fumarate as final electron acceptor. This metabolic feature makes it one of the ideal candidates for developing biotechnological industrial routes that could eventually replace the polluting and environment unfriendly petrochemical ones that are still main sources in the production of this value added compound. In fact, due to the wide number of applications of succinic acid, that range from the more traditional ones as food additive or pharmaceutical intermediate, to the latest uses as building block for biopolymers and bioplastic, increasing demand and market size growth are expected in the next years. In line with a “green revolution” needed to preserve our environment, the great challenge is the establishment of commercially viable production processes that exploit renewable materials and in particular preferably non –food lignocellulosic biomasses and waste products. In this review we describe the currently available literature involving B. succiniciproducens since the strain was firstly isolated, focusing on the different renewable materials and fermentation strategies used to improve succinic acid production titers up to date. Moreover, an insight into the metabolic engineering approaches and the key physiological characteristics of B. succiniciproducens deducted from the different studies are presented.